Phenotypic variability in 49 cases of ESCO2 mutations, including novel missense and codon deletion in the acetyltransferase domain, correlates with ESCO2 expression and establishes the clinical criteria for Roberts syndrome. Issue 1 (1st July 2009) - Vega, H; Trainer, A H; Gordillo, M; Crosier, M; Kayserili, H; Skovby, F; Uzielli, M L Giovannucci; Schnur, R E; Manouvrier, S; Blair, E; Hurst, J A; Forzano, F; et al.
Abstract : Background: Roberts syndrome (RBS) and SC phocomelia are caused by mutations in ESCO2, which codes for an acetyltransferase involved in the regulation of sister chromatid cohesion. Of 26 mutations described to date, only one missense mutation has been reported and all others are predicted to be truncating mutations. Genotype–phenotype analysis has been hampered by limited numbers of patients with clinical information available. Objective: To provide unpublished clinical data for 31 patients with proven ESCO2 mutations and combine this series with previously reported clinical and mutation data on 18 cases. Methods: Genotype–phenotype correlations and functional effects of two novel ESCO2 mutations were analysed. In situ hybridisation on human embryos at Carnegie stages 14, 17 and 21 was performed to study ESCO2 expression during development. Results and conclusions: Using the cohort of 49 patients, the clinical criteria for RBS were delineated to include: growth retardation; symmetric mesomelic shortening of the limbs in which the upper limbs are more commonly and severely affected than the lower limbs; characteristic facies with microcephaly. The severity of malformations of the facies correlates with the severity of limb reduction. The occurrence of corneal opacities may be associated with specific mutations. Two new mutations, both in the ESCO2 acetyltransferase domain, are described and their acetylation effects in vitro demonstrated. In situ hybridisation on human embryos showed ESCO2 expression in the brain, face, limb, kidney and gonads, which corresponds to the structures affected in RBS.